Android application development for dummies - Burton, Michael (For dummies, 2015)
This book will show you: how to build a great app with Android Studio; how to create an app widget; when to use advanced techniques, such as Fragments, Databases, and Image Downloads; Material Design to beautify your app; ways to build apps on Android and Amazon tablets; how to create apps for Android Wear and TV. --